2021
DOI: 10.1037/ebs0000199
|View full text |Cite
|
Sign up to set email alerts
|

Missed connections and embarrassing confessions: Using big data to examine sex differences in sexual omission and commission regret.

Abstract: Error management theory (EMT; Haselton & Buss, 2000) draws on parental investment theory (Trivers, 1972) and signal detection to make novel predictions about human cognitive biases and their adaptive implications. EMT predicts that heterosexual men overperceive sexual interest from women, whereas women underperceive honest signals of relationship commitment from men. In turn, sexual strategies theory (Buss & Schmitt, 1993) predicts that men may experience more regret over romantic or sexual omission (missed op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Consistent with sexual strategies theory, men were more willing than women were to engage in a short-term sexual relationship (Buss and Schmitt 1993), a finding that extended even to prospective mates of low physical attractiveness (H1). This is also consistent with error management theory (Haselton and Buss 2000;Perilloux 2014) in that, even though men tend to place greater value on physical attractiveness (Buss and Schmitt 1993;Confer et al 2010;Jonason et al 2012b;Li et al 2002;Regan 1998a, b), in a low risk, short-term context, men were willing to form a relationship with a physically unattractive mate to avoid missing out on a mating opportunity (Jonason et al 2020a, b;Regan 1998a, b;Webster et al 2020). In addition, both sexes reported lower levels of interest in prospective mates after learning that the potential mate possessed dealbreakers rather than dealmakers (H4).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Consistent with sexual strategies theory, men were more willing than women were to engage in a short-term sexual relationship (Buss and Schmitt 1993), a finding that extended even to prospective mates of low physical attractiveness (H1). This is also consistent with error management theory (Haselton and Buss 2000;Perilloux 2014) in that, even though men tend to place greater value on physical attractiveness (Buss and Schmitt 1993;Confer et al 2010;Jonason et al 2012b;Li et al 2002;Regan 1998a, b), in a low risk, short-term context, men were willing to form a relationship with a physically unattractive mate to avoid missing out on a mating opportunity (Jonason et al 2020a, b;Regan 1998a, b;Webster et al 2020). In addition, both sexes reported lower levels of interest in prospective mates after learning that the potential mate possessed dealbreakers rather than dealmakers (H4).…”
Section: Discussionsupporting
confidence: 66%
“…This suggests that men will be less open to dating someone who is below average in physical attractiveness (Gangestad et al 2006;Li et al 2002). However, error management theory (Haselton and Buss 2000;Perilloux 2014) suggests that, whenever mating options are sub-par, men may be willing to overlook their preferences for physical attractiveness to not miss out on a reproductive opportunity, especially if the mating context is short-term and the prospective mate possesses dealmakers (Webster et al 2020). In this study, we examined men and women's ratings of prospective mates in both long-term and short-term contexts when these mates were physically unattractive and possessed either favorable (i.e., dealmakers) or unfavorable (i.e., dealbreakers) characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media investment behavior after the relationship has ended was more common for men and for younger people. Men are more likely to experience sexual omission regret including “the one who got away” phenomenon (Webster et al, 2020), which may manifest as reaching out to former partners. Men may also wish to avoid any potential reputational damage that could result from the loss of a partner, particularly if they did not initiate the dissolution (Perilloux & Buss, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A commonly held belief is that women tend to have negative experiences from casual sex. Indeed, past research has found that casual sex is associated with higher regret, distress, suicidal thought, depression, and guilt, as well as lower self-esteem in women (Bersamin et al, 2014;Dubé et al, 2017;Fisher et al, 2012;Grello et al, 2006;Paul et al, 2000;Sandberg-Thoma & Kamp Dush, 2014;Webster et al, 2020). Regarding sexual function and satisfaction, women also experience lower rates of orgasm in casual sex compared to sex in a committed relationship (Armstrong et al, 2012;Wongsomboon et al, 2020).…”
Section: It's the "Why": Links Between (Non)autonomous Sexual Motives Sexual Assertiveness And Women's Orgasm In Casual Sexmentioning
confidence: 98%